Electroless Deposited Nickel Thin Films Alloyed with Thorium. Issue 8 (21st April 2022) - Schapiro, Ilan; Shandalov, Michael; Maman, Nitzan; Ezersky, Vladimir; Golan, Yuval; Yahel, Eyal
Abstract: Ni thin films alloyed with 232 Th are obtained using electroless bath deposition by optimization of solution composition and deposition temperature. X‐ray photoelectron spectroscopy and transmission electron microscopy (TEM) indicate a fairly homogenous distribution of 232 Th, with considerable amounts of incorporated oxygen. TEM confirms the presence of crystalline films with low concentrations of nickel phosphide precipitates for both non‐alloyed Ni and Ni─Th films. Abstract : Ni thin films alloyed with 232 Th are obtained using electroless bath deposition. XPS and transmission electron microscopy (TEM) indicate a fairly homogenous distribution of 232 Th, with considerable amounts of incorporated oxygen. TEM confirms the presence of crystalline films with low concentrations of nickel phosphide precipitates for both non‐alloyed Ni and Ni─Th films.